Investigation of patients with unclassified bleeding disorder and abnormal thrombin generation for physiological coagulation inhibitors reveals multiple abnormalities and a subset of patients with increased tissue factor pathway inhibitor activity. (31st January 2020) - MacDonald, Stephen; White, Danielle; Langdown, Jon; Downes, Kate; Thomas, Will
Abstract: Introduction: We have routinely used thrombin generation to investigate patients with unclassified bleeding disorder (UBD). Aims: To investigate haemostatic abnormalities in patients with UBD that had abnormal thrombin generation on at least one occasion. Methods: Investigation of 13 known UBD patients with thrombin generation and detailed haemostatic testing was undertaken including TFPI assays but also thrombomodulin and fibrinogen‐ γ . Results: 12 females and 1 male were included. No patient had a platelet function disorder or coagulation factor deficiency that explained the bleeding phenotype, though 2 patients had factor deficiencies; a factor X of 0.41 IU/mL and a factor XI of 0.51 IU/mL. ThromboGenomics revealed variants for these factors but no other abnormalities. Patients were included who previously had either prolonged lag time or decreased endogenous thrombin potential (ETP) via high dose tissue factor (5 pmol/L) or low dose tissue factor (1.5 pmol/L) with corn trypsin inhibitor (CTI). Tissue factor pathway inhibitor (TFPI) activity was significantly increased ( P  < .001; increased in 8 patients) compared with controls and abnormalities in soluble thrombomodulin (2 patients), fibrinogen‐γ (1 patient) and tPA (4 patients for each) were seen. Total and free TFPI levels were not increased. Mixing studies of patient plasma with 50:50 normal plasma for thrombin generation via low dose tissue factor failed to correct the ETP consistent with ongoing inhibition. Addition of an anti‐TFPI antibody partially corrected thrombin generation to normal levels. TFPI sequencing was unremarkable. Conclusion: TFPI activity may be increased in a subset of UBD patients. Further research studies are warranted in UBD patients for coagulation inhibitor abnormalities.